Universitas Kristen Satya Wacana students' understanding of public relations profession: A phenomenology - Parastiwi, Nadia; Darmastuti, Rini (Jurnal Studi Komunikasi, 2020)
There have been various definitions of the Public Relation profession related to its purposes since its birth in the 1960s. The current research investigated is the meaning of the Public Relations profession for Public Relations students at Universitas Kristen Satya Wacana who, in the future, would work as Public Relations. This research was conducted using qualitative methods and a phenomenological approach. Three findings were presented in this article. First, the construction of the Public Relation profession depends on the body of knowledge, the ability to communicate and build relationships with the community, be creative, and have an attractive appearance. Second, the meaning of the Public Relation profession is constructed based on four references, namely the media and the surrounding community, materials and classes in higher education, from practitioners and developments in information technology. Third, the construction of the identity of the Public Relations profession through online shopping to improve self-image, obtain information on fashion developments, and the ability to select products selectively.